Clonal structure and the specificity of vaccine-induced T cell response to SARS-CoV-2 Spike protein - Sheetikov, Saveliy A.; Khmelevskaya, Alexandra A.; Zornikova, Ksenia V.; Zvyagin, Ivan V.; Shomuradova, Alina S.; Serdyuk, Yana V.; Shakirova, Naina T.; Peshkova, Iuliia O.; Titov, Aleksei; Romaniuk, Dmitrii S.; Shagina, Irina A.; Chudakov, Dmitry M.; et al. (Frontiers in Immunology, 2024)
Adenovirus vaccines, particularly the COVID-19 Ad5-nCoV adenovirus vaccine, have emerged as promising tools in the fight against infectious diseases. In this study, we investigated the structure of the T cell response to the Spike protein of the SARS-CoV-2 virus used in the COVID-19 Ad5-nCoV adenoviral vaccine in a phase 3 clinical trial (NCT04540419).In 69 participants, we collected peripheral blood samples at four time points after vaccination or placebo injection. Sequencing of T cell receptor repertoires from Spike-stimulated T cell cultures at day 14 from 17 vaccinated revealed a more diverse CD4 + T cell repertoire compared to CD8 + . Nevertheless, CD8 + clonotypes accounted for more than half of the Spike-specific repertoire.Our longitudinal analysis showed a peak T cell response at day 14, followed by a decline until month 6. Remarkably, multiple T cell clonotypes persisted for at least 6 months after vaccination, as demonstrated by ex vivo stimulation. Examination of CDR3 regions revealed homologous sequences in both CD4 + and CD8 + clonotypes, with major CD8 + clonotypes sharing high similarity with annotated sequences specific for the NYNYLYRLF peptide, suggesting potential immunodominance.In conclusion, our study demonstrates the immunogenicity of the Ad5-nCoV adenoviral vaccine and highlights its ability to induce robust and durable T cell responses. These findings provide valuable insight into the efficacy of the vaccine against COVID-19 and provide critical information for ongoing efforts to control infectious diseases.